Modeling of microstructure evolution coupled with molten pool oscillation during electron beam welding of an Al-Cu alloy. (15th June 2022) - Yang, Ziyou; Fang, Hui; Jin, Kangning; He, Jingshan; Ge, Wenjun; Yan, Wentao
Highlights: A multi-physics modeling framework is adopted to study complex solidification behavior in the EBW. The mechanism of microstructure evolution under the effect of molten pool oscillation is revealed. Grain morphology, grain size, segregation and second phase are quantitatively predicted. Predicted results are compared to experimental observations and measurements. Abstract: The physical understanding of electron beam welding (EBW) and prediction of the weld microstructure are valuable but challenging. In this work, a multi-physics modeling framework is adopted to simulate the microstructure evolution during the EBW process. A molten pool model incorporating multiple driving forces and a dynamic heat source model provides the temperature field as the input for the microstructure simulation. Both the temperature and chemical concentration are considered in the grain growth process. Additionally, an efficient method is adopted to track the second phase in the solidification process, and a practical algorithm is proposed to identify the complex weld shapes. The mechanism of microstructure evolution under the effect of molten pool oscillation is elaborated. Based on the simulated results, the effects of the process parameters on the grain morphology, grain size, segregation and second phase are quantified. These predicted results are compared to experimental observations and measurements. This study could be helpful for both understanding microstructure evolution and optimizing the actual welding process to tailor the microstructure.